RHETORICAL PATTERNS, VERB TENSE, AND VOICE IN CROSS DISCIPLINARY RESEARCH ARTICLE ABSTRACT - Sharifah Hanidar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This article investigates research article abstracts in terms of their rhetorical patterns and the use of verb tenses and voice. A total of 40 abstracts were selected from four international journals in the fields of Biology, Mechanical Engineering, Linguistics, and Medicine. A four move model was adopted from Hardjanto (1997) to analyze the structure of the abstracts. The results show that all the abstracts have Move 1, creating a research space; 70% have Move 2, describing research procedure; 85% have Move 3, summarizing principal results; and 85% have Move 4, evaluating results. All the abstracts in medicine have Moves 1, 2, 3 and 4, whereas the most common pattern in Biology is Moves 1, 3 and 4, in Mechanical Engineering Moves 1, 2 and 3, and in Linguistics Moves 1, 2 and 4. This seems to suggest that there is a disciplinary variation in the structuring of RA abstracts in the four disciplines under investigation. With regard to the use of verb tense and voice in each move, the present tense and past tense in the active voice and the past tense in the passive voice were the most frequently used tenses. The present tense in the active voice was frequently used in Moves 1 and 4, while the past tense in the active voice was commonly used in Move 3 and the past tense in the passive voice was frequently found in Move 2. Furthermore, it was found that the present tense in the active voice was frequently used in Biology, Mechanical Engineering and Linguistics, whereas the past tense in the active voice occurred more frequently in Medicine, and the past tense in the passive voice was more frequently found in Mechanical Engineering than in other disciplines.